Screening for co‐occurring conditions in adults with autism spectrum disorder using the strengths and difficulties questionnaire: A pilot study. Issue 12 (28th March 2016) - Findon, James; Cadman, Tim; Stewart, Catherine S.; Woodhouse, Emma; Eklund, Hanna; Hayward, Hannah; De Le Harpe Golden, Daniel; Chaplin, Eddie; Glaser, Karen; Simonoff, Emily; Murphy, Declan; Bolton, Patrick F.; et al.
Abstract : Adolescents and adults with autism spectrum disorder (ASD) are at elevated risk of co‐occurring mental health problems. These are often undiagnosed, can cause significant impairment, and place a very high burden on family and carers. Detecting co‐occurring disorders is extremely important. However, there is no validated screening tool for this purpose. The aim of this pilot study is to test the utility of the strengths and difficulties questionnaire (SDQ) to screen for co‐occurring emotional disorders and hyperactivity in adolescents and adults with ASD. The SDQ was completed by 126 parents and 98 individuals with ASD (in 79 cases both parent and self‐report were available from the same families). Inter‐rater reliability, test‐retest stability, internal consistency, and construct validity were examined. SDQ subscales were also compared to clinically utilized measures of emotional disorders and hyperactivity to establish the ability to predict risk of disorder. Inter‐rater reliability ( r  = 0.42), test‐retest stability ( r  = 0.64), internal consistency ( α  = 0.52–0.81) and construct validity ( r  = 0.42–0.57) for the SDQ subscales were comparable to general population samples. Parent‐ and self‐report SDQ subscales were significantly associated with measures of anxiety, depression and hyperactivity (62–74% correctly classified). Parent‐report performed significantly better than self‐report; adults with ASD under‐reported difficulties. The SDQ shows promise as a simple and efficient way to screen for emotional disorders and hyperactivity in adolescents and adults with ASD that could help reduce the impact of these disorders on individuals and their families. However, further more systematic attempts at validation are warranted. Autism Res 2016, 9: 1353–1363 . © 2016 International Society for Autism Research, Wiley Periodicals, Inc.